2022
DOI: 10.3390/jcm11123396
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial Patency Rates of Hepatico-Jejunal Anastomosis after Repair of Bile Duct Injury at a Reference Center

Abstract: Background: Bile duct injury complicates patients’ lives, despite the subsequent repair. Repairing the injury must restore continuity of the bile tree and bring the patient into a state of cure referred to as “patency”. Actuarial primary or actuarial secondary patency rates, depending on whether the patient underwent primary or secondary repair of injury, are proposed to be a proper metric in evaluating outcomes. This study was undertaken to assess outcomes of 669 patients with bile duct injuries Strasberg D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…The key to the successful repair of high-level bile duct injury is the exposure of the damaged bile duct opening. This often requires descending or perihilar resection to repair the normal bile duct opening and then complete Roux-en-Y hepaticojejunostomy [18][19]. In clinical practice, 3D visualization technology has been well applied in the perihilar resection of hilar cholangiocarcinoma [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The key to the successful repair of high-level bile duct injury is the exposure of the damaged bile duct opening. This often requires descending or perihilar resection to repair the normal bile duct opening and then complete Roux-en-Y hepaticojejunostomy [18][19]. In clinical practice, 3D visualization technology has been well applied in the perihilar resection of hilar cholangiocarcinoma [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all relevant studies have shown that the timing of sound biliary repair by experienced surgeons is a critical factor in improving the prognosis of BDI patients 5 , 22 24 . Previous studies revealed that the success rate of repair performed by specialists can reach 79%; however, it is lower than 30% in the case of nonspecialists or beginners 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Конечно, вопрос о выборе времени для реконструктив ной операции является в настоящее время открытым и требует консенсуса, обозначенного клиническими рекомендациями [27]. С каждой последующей реопера цией шансы на развитие стриктуры анастомоза увели чиваются [28,29]. Что касается послеоперационной диагностики повреж дения желчных протоков, то наиболее ранними сим птомами являются боль в животе, напряжение мышц передней брюшной стенки, повышение температуры, тошнота и рвота, появление желтухи.…”
Section: с оврем енны й подход к реконст рукц ииunclassified